(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to derive basic and integrative science processes and thinking skills from some The verses of the Holy Qur’an explain how to link their applications in teaching science. Follow the deductive method that hangsHe derives a sub-rule from a general ruling found in one or more verses of the Holy Qur’an, and suffices to prove it.With some examples without resorting to extrapolating them all, it turns out that the Holy Qur’an is replete with basic science operationsAnd complementarity and thinking skills, which are the procedural side of science through which the side is reachedCognitive science The current research was satisfied with demonstrating the procedural side with some selected verses fromThe Holy Quran ; Examples of science processes that the current research investigated and revealed are the basic Holy Quran:Observation; Measurement to classify inference, extrapolation, deduction, prediction, use of numbers, communication, and fromExamples of complementary science operations: Imposing hypotheses Interpretation Procedural definitions » Adjusting variables ©experimentation; The current research also found that the Holy Qur’an is full of various thinking skills, including thinking skillsInnovative derived from the Holy Quran: originality; flexibility; fluency sensitivity to problems; realizedetails thinking about thinking reflective thinking; In addition to thinking skills: remembering to ask questions;The transition from cognitive imbalance to cognitive equilibrium, comparison; arrangement » representation; imagination; summary;Make decision.